PHUBBING DAN DAMPAKNYA PADA REMAJA: PROGRAM EDUKASI UNTUK MENINGKATKAN INTERAKSI SOSIAL TANPA GANGGUAN DIGITAL - Fathurrahman, Muhammad; Ulfah, Yetty Faridatul; Liswara, Musa Ahmad; Ibad, Taqwa Nur (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
The development of digital technology has given rise to the phenomenon of phubbing (ignoring conversation partners in favor of gadgets), which negatively impacts social interaction, mental health, and adolescents' emotional development. This community service program aims to raise awareness about the effects of phubbing and train students in digital-free social interaction skills among junior high school students at SMP Negeri 1 Andong, Boyolali. The methods used include interactive seminar-based counseling, group discussions, and role-play simulations to encourage active participation. Evaluation results show a significant improvement in participants' understanding, with 85% able to explain the impacts of phubbing (up from 38% in the pre-test), and 60% reporting a reduction in phubbing behavior within two weeks post-intervention. Constraints such as time limitations and facility shortages were addressed by adapting methods and collaborating with teachers and parents. The program recommends integrating anti-phubbing materials into school activities and daily life, establishing